Preparation, spectral characterization and antibacterial studies of silver(I) complexes of 2-mercaptopyridine and thiomalate. Issue 1 (2008) - Hanif Hanif, Muhammad Muhammad; Saddiqa Saddiqa, Aisha Aisha; Hasnain Hasnain, Shahida Shahida; Ahmad Ahmad, Saeed Saeed; Rabbani Rabbani, Ghulam Ghulam; Isab Isab, Anvarhusein A. Anvarhusein A.
Abstract : Silver(I) complexes of 2-mercaptopyridine (Mpy), [Ag(Mpy)]NO3 and [Ag(Mpy)2 ]NO3, and the first mixed-ligand complex having a thione and thiolate coordinated to Ag(I), [Mpy–Ag–Tm] (Tm═thiomalate) have been prepared and characterized by IR and NMR spectroscopy. The 1 H and 13 C NMR spectra show the presence of both ligands in the mixed-ligand complex, [Mpy–Ag–Tm]. An upfield shift is observed in the >C═S resonance of Mpy and C═O resonances of thiomalate in 13 C NMR, while the other resonances are shifted downfield. The complexes showed relatively high antibacterial activity (inhibition zone of 6–11 mm) against a gram +ve bacterium, Bacillus subtilis, as compared to that (inhibition zone of 4 mm) against a gram –ve bacterium, Escherichia coli .